Penggunaan Embedded Correlational Mixed Methods Approach Model untuk Pengukuran kompetensi kepribadian dan Kinerja - Wardoyo, Cipto (Jurnal Aplikasi Manajemen, 2012)
Law of the Republic of Indonesia No. 14/2005 on Teachers and Lecturers called the four competencies of teachers, which include: pedagogical competencies, personality, social, and professional; fourth is a component of professional competence of teachers; with variable compensation determines the quality of performance. The purpose of this study to see the professionalism and the influence of variable compensation to performance. The approach used is a combination/mix (embedded correlational mixed methods approach model) exclusively for personal competency variables that serve to support the findings of expost facto quantitative approach to the design. Number of samples 76 teachers (50%) of the total population in Malang. Analysis of data using multiple regression techniques and sequential analysis of data. The study's findings that the pedagogic competence, personality and professional significant effect on teacher performance, social competence, and the compensation effect is not significant. Competence of the personality of the results of interviews indicate that at first not interested in being a teacher, but is becoming interested and fun, so it performs well, this means finding qualitatively supports the findings of the quantitative approach.